Reconstructing deep‐time palaeoclimate legacies in the clusioid Malpighiales unveils their role in the evolution and extinction of the boreotropical flora. Issue 5 (24th March 2018) - Meseguer, Andrea S.; Lobo, Jorge M.; Cornuault, Josselin; Beerling, David; Ruhfel, Brad R.; Davis, Charles C.; Jousselin, Emmanuelle; Sanmartín, Isabel
Abstract: Aim: During its entire history, the Earth has gone through periods of climate change similar in scale and pace to the warming trend observed today in the Anthropocene. The impact of these ancient climatic events on the evolutionary trajectories of organisms provides clues on the organismal response to climate change, including extinction, migration and persistence. Here, we examine the evolutionary response to climate cooling/warming events of the clusioid families Calophyllaceae, Podostemaceae and Hypericaceae (CPH clade) and the genus Hypericum as test cases. Location: Holarctic. Time period: Late Cretaceous–Cenozoic. Major taxa studied: Angiosperms. Methods: We use palaeoclimate simulations, species distribution models and phylogenetic comparative approaches calibrated with fossils. Results: Ancestral CPH lineages could have been distributed in the Holarctic 100 Ma, occupying tropical subhumid assemblages, a finding supported by the fossil record. Expansion to closed‐canopy tropical rain forest habitats occurred after 60 Ma, in the Cenozoic, in agreement with earlier ideas of a post‐Cretaceous origin of current tropical rain forest. Posterior Cooling during the Eocene triggered diversification declines in CPH tropical lineages, and was associated with a climatic shift towards temperate affinities in Hypericum . Hypericum subsequently migrated to tropical mountains, where it encountered different temperate conditions than in the Holarctic. Main conclusions: We hypothesize that most clusioid CPH lineages failed to adapt to temperate regimes during periods of Cenozoic climate change, and went extinct in the Holarctic. In contrast, boreotropical descendants including Hypericum that underwent niche evolution demonstrated selective advantages as climates became colder. Our results point toward macroevolutionary trajectories involving the altering fates of closely related clades that adapt to periods of global climate change versus those that do not. Moreover, they suggest the hypothesis that potentially many clades, particularly inhabitants of boreotropical floras, were likely extirpated from the Holarctic and persist today (if at all) in more southern tropical locations.